KARAKTERISASI DAN SKRINING FITOKIMIA SERTA ANALISIS FLAVONOID DARI BUAH MENGKUDU (Morindacitrifolia L) SECARA KROMATOGRAFI LAPIS TIPIS - Sitorus, Panal; Suharyanisa, Suharyanisa; Chandra, Devina; Nurbaya, Siti; Sitanggang, Berton (Jurnal Farmanesia, 2021)
Noni fruit (Morindacitrifolia L.) is a medicinal plant that is well known by the people in Indonesia. Noni is efficacious as an immune enhancer, normalizes blood pressure, anti-cancer, analgesic, diabetes mellitus, heart disease, stroke, antimicrobial. To know the characteristics of simplicia and the class of compounds from the noni fruit as well as to analyze the flavonoid compounds contained in the noni fruit using the thin layer chromatography method. The flavonoid compounds were extracted by maceration using ethanol solvent and then the ethanol extract was tested by thin-layer chromatography using 1% HCl mobile phase and spotting with 1 N H2SO4 reagent and methanol pa (1: 1% v/v). Result of simplicia characterization of fruit Noni, obtained 1.32% water content, 38.41 % water soluble extract content, 16.7% ethanol soluble extract content, 6.09% total ash content, and 0.45 acid insoluble ash content. %. Noni fruit simplicia contains chemical compounds of alkaloids, tannins, flavonoids, triterpenoids/steroids, anthraquinones, saponins with phytochemical screening tests. The value of Rf from the analysis of noni fruit flavonoid compounds using the Thin Layer Chromatography method with 3 repetitions is 0.75; 0.68 and 0.62. This indicates the presence of flavonoid compounds in the noni fruit.